Cloud Based Secured Log Retrieval Using Fully Homomorphic Encryption - Rasina Begum, B.; Chithra, P. (Asian Journal of Engineering and Applied Technology, 2020)
Cloud computing provides a scalable platform for growing amount of data and processes that work on various applications and services by means of on-demand service providing. The storage services offered by clouds have become a new profit growth by providing a comparably cheapest, scalable, location-independent platform for managing users’ data. Client uses the cloud storage and enjoys the high-quality applications and services from a shared pool of configurable computing resources using cloud services. It reduces the trouble of local data storage and maintenance. But it gives severe security threats toward users’ outsourced data. Maintaining the log record securely over extended period is very crucial to the proper functioning of any organization. Log holds the record of system events specially user activities. It is the main target for malicious attackers. An attacker, breaking into a system would not try to leave traces of his or her activities behind. This proposed work mainly concentrates on the problem of log security in cloud computing system and using fully homomorphism encryption algorithm in the cloud computing log data.